Специфічні чинники девіантної поведінки військовослужбовців - Худавердова, А. О.; Khudaverdova, A. O. (Вісник Львівського університету. Сер.: Психологічні науки. - 2021. - Вип.11. - С. 225-230, 2021)
Проаналізовано специфічні чинники, форми виявів і причини девіантної поведінки військовослужбовців. Зазначено, що відхилення від соціальних норм у поведінці військовослужбовців пов’язані з особливостями проходження військової служби, жорсткою субординацією, чіткою регламентацією діяльності та поведінки військовослужбовців, необхідністю суворого і точного дотримання вимог військових статутів, наказів, указівок, інструкцій і настанов. Виявлено діагностичні індикатори схильності до порушення службової (військової) дисципліни. Девіантну поведінку військовослужбовців у статті розглянуто як таку, що характеризується наявністю в поведінці однієї або кількох девіацій, пов’язаних із правопорушеннями, алкоголізмом, наркоманією, токсикоманією, суїцидом, бродяжництвом, жебракуванням, взаємодією військовослужбовців, що містить потенційну соціальну небезпеку, призводить до особистісної деградації та виявляється в єдності мотиваційних, особистісно-смислових та нормативно-діяльнісних характеристик. Наголошено на важливості психологічної діагностики особистісних особливостей військовослужбовців із метою попередження та профілактики їхньої неправової поведінки.

In the article the specific factors, forms of manifestations and causes of deviant behaviour of military service members have analysed. It is noted, that deviations from social norms in the behaviour of military service members are associated with the peculiarities of military service, strict subordination, clear regulation of activities and behaviour of the military personnel, the need for strict and precise compliance with military statutes, orders, instructions and guidelines. Diagnostic indicators of propensity to professional (military) misconduct have been identified. It is noted that service in the army is characterized by: monotony, changed spatial and temporal perception, limitation of personally significant information, loneliness, group isolation (information exhaustion of communication partners, constant publicity, etc.) and the presence of life-threatening. All this tests the moral and psychological stability of military service members and can lead to deviations. The psychological problems of the period of adaptation of conscripts to military service are highlighted: problems of getting used to the conditions of military service (manifested in demonstrative behaviour, tearfulness, desire to evoke sympathy, low activity, infantilism, etc.); emergence of hazing (signs - depression, night insomnia, desire to go to work, study, etc.); personal problems related to family, gender relations (signs - the tendency to use the phone often, computer communication, lack of concentration, detachment, etc.). In the article deviant behaviour of military personnel is considered as characterized by the presence in the behaviour of a person of one or more deviations associated with offenses, alcoholism, drug addiction, substance abuse, suicide, vagrancy, begging, leads to personal degradation and is manifested in the unity of motivational, personal-semantic and normative-activity characteristics. The importance of psychological diagnosis of personal characteristics of military service members in order to prevent and prevent their unlawful behaviour is emphasized.

Проанализированы специфические факторы, формы проявлений и причины девиантного поведения военнослужащих. Отмечено, что отклонение от социальных норм в поведении военнослужащих связано с особенностями прохождения военной службы, жесткой субординацией, четкой регламентацией деятельности и поведения военнослужащих, необходимостью строгого и точного соблюдения требований военных уставов, приказов, указаний, инструкций и установок. Выявлены диагностические индикаторы склонности к нарушению служебной (военной) дисциплины. Девиантное поведение военнослужащих в статье рассмотрено как характеризующееся наличием в поведении одной или нескольких девиаций, связанных с правонарушениями, алкоголизмом, наркоманией, токсикоманией, суицидом, бродяжничеством, попрошайничеством, взаимодействием военнослужащих, содержащей потенциальную социальную опасность и выражается в единстве мотивационных, личностно-смысловых и нормативно-деятельных характеристик. Отмечено важность психологической диагностики личностных особенностей военнослужащих с целью предупреждения и профилактики их неправового поведения.
Specific factors of deviant behaviour of military servants
Худавердова, А. Специфічні чинники девіантної поведінки військовослужбовців / Анна Худавердова / Вісник Львівського університету. Сер.: Психологічні науки. - 2021. - Вип.11. - С. 225-230. -DOI: https://doi.org/10.30970/PS.2021.11.27.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; девіантна поведінка; deviant behavior; девиантное поведение; девіації; deviations; девиации; військовослужбовці; military servants; военнослужащие; відхилення від соціальних норм; deviations from social norms; отклонение от социальных норм; групова ізоляція; group isolation; групповая изоляция; нестатутні відносини; non-statutory relations; неуставные отношения